Customer relationship management in Singapore's food court market. Myth or reality? - Lim, Collin Lee Leng (2007)
Recent developments in the field of marketing research and the highly competitive nature of the business world have led to organizations to focus on using Customer Relationship Management (CRM) as a useful and important tool to enable such organizations to maximize corporate growth and garner significant profitability. However, the process of carrying out CRM is a two way process involving both the organizations implementing CRM to the targeted customers and the customersÃÂÃÂ¢ÃÂÃÂÃÂÃÂ acceptance level to such relationship building. Evidence of such relationship building can be found distinctly in the banking and telecommunication industries.